Bir eğitim modeli olarak, köy enstitülerinde müzik eğitiminin incelenmesi ve şarkı dağarcığının kullanılabilirliği - Kar, Tuğçem (My University, 2008)
BİR EĞİTİM MODELİ OLARAK KÖY ENSTİTÜLERİNDE MÜZİK EĞİTİMİNİN İNCELENMESİ VE ŞARKI DAĞARCIĞININ KULLANILABİLİRLİĞİ Bu araştırma, “Bir Eğitim Modeli Olarak Köy Enstitülerinde Müzik Eğitiminin İncelenmesi ve Şarkı Dağarcığının Kullanılabilirliği”ni ölçmek amacıyla yapılmıştır. Araştırmada; Bir eğitim modeli olarak; 1940–1950 yılları arasında eğitim / öğretim sürecini devam ettirmiş olan Köy Enstitülerinin müzik eğitimi programının incelenmesi; 21 Köy Enstitüsünün mezunları ile yapılacak olan görüşmeler sonucunda Köy Enstitüleri müzik eğitimi programının nasıl uygulandığının incelenmesi; Köy Enstitüleri müzik eğitimi programının günümüzde uygulanabilirliğinin araştırılması amaçlanmıştır. Ayrıca; Köy Enstitülerinde kullanılan müzik eğitimi dağarcığının bulunması ve bugünkü kullanılabilirliğinin anket yoluyla incelenmesi ve bir derleme oluşturulabilmesi hedeflenmektedir. Bu bağlamda öncelikle Köy Enstitüsü Programlarının Etkilendiği Eğitim Sistemlerini inceleme yoluna gidilmiştir. John Dewey, Georg Kerchensteiner, Heinrich Pestalozzi, Emile Jacques Dalcroze, Zoltan Kodally, Carl Orff, Shnichi Suzuki gibi pedagoglara ve Konstrüktivizm “Oluşturmacılık” eğitim anlayışına ulaşılmıştır. Daha sonra da İsmail Hakkı Tonguç’un Eğitim anlayışı ve Köy Enstitüleri Öğretim Programlarının incelenmesine yer verilmiştir. Köy Enstitülerindeki müzik eğitimi programının nasıl uygulandığının araştırılması için yürütülen röportajlarda araştırmanın evrenini 21 Köy Enstitüsünün tüm mezunları; örneklemini ise çalışma evreni arasından seçilen 15 adet Köy Enstitüsü mezunu oluşturmuştur. Köy Enstitüleri şarkı dağarcığının kullanılabilirliğinin araştırılması için yürütülen anket çalışmasında araştırmanın evrenini ilköğretimde görev yapan tüm müzik öğretmenleri; örneklemini ise çalışma evreni arasından seçilen 100 adet müzik öğretmeni oluşturmuştur. Araştırma verileri görüşme, kaynak tarama ve anket yöntemiyle elde edilerek, betimsel istatistik yöntemlerine göre çözümlenmiştir. Araştırmada; Bir eğitim modeli olarak; Köy Enstitülerindeki müzik eğitimi programının nasıl uygulandığı incelenmiş, bulgular yüzde frekans analizine göre değerlendirilerek yorumlanmış ve öneriler getirilmiştir. Enstitüleri, Müzik Eğitimi.

THE RESEARCH OF APPLICABILITY AND PRACTICABILITY THE MUSIC EDUCATION AND SONG REPERTORIES OF VILLAGE INSTUTES AS AN EDUCATION MODEL This research Project has been made in order to analyse and examine the Musical Teaching and the research of applicability and practicability of Song Repertories of Village Insitutes as an Educational Model. In this Master Thesis project; the examination of the Musical Teaching Programmes, as a Teaching Model, at Village Institutes which are Governmental Education Insitutions that exist between the years 1940 – 1950, is aimed. The understanding of the applications of Musical Teaching Programmes at Village Institutes, with regard to the Interviews that are going to be made with the Graduates from 21 Village Institutes who are still alive is also purposed. As a result, by obtaining these datas, the applicability of Musical Teaching Methods used at Village Institutes to todays’ Musical Teaching discipline could be interpreted. Moreover, finding the Repertories’ of Musical Teaching at Village Institutes and the research of its applicability to todays’ Musical Teaching Repertories’ by the help of questionnaire results among the Primary School Music Teachers, and an anthology or a compilation with regard to these survey results are purposed. Concerning the above mentioned purposes, principally the Analysis of the Educational Systems that effect the Village Institutes’ Programmes are taken into consideration. Consequently these seekings lead us to the Pedagogues; John Dewey, Georg Kerchensteiner, Heinrich Pestalozzi, Emile Jacques Dalcroze, Zoltan Kodally, Carl Orff, Shnichi Suzuki and the Constructivist Educational Conception. After all, the Educational Conception of İsmail Hakkı Tonguç and the Village Institutes Educational Programmes have been examined. In order to find out the applicability of Musical Teaching Programmes at Village Institutes, set of Interviews have been planned among the 21 Village Institutes’ entire Graduates and after a precise and detailed research and investigation valuable and useful interviews have been concluded with the 15 Village Institute Graduates. As a result of Questionnaire Survey which is made in order to find out the applicability of the Song Repertories’ of Village Institutes to todays’ Musical Teaching Repertories’, the target group have been chosen as the Primary School Music Teachers. After an exhaustive and pleasant research the chosen 100 Primary School Music Teachers have completed the Questionnaire Survey. The research datas have been obtained by the help of interviews, resource research, and questionnaire surveys and the analysis have been achieved by using the figurative statistical methods. Key Words: Village Institute, Music Education.
Keywords: Müzik eğitimi